ASPEK HUKUM BISNIS DALAM PENGEMBANGAN PENGELOLAAN PARIWISATA DI PULAU-PULAU KECIL - Aartje Tehupeiory (Fakultas Hukum Universitas Kristen Indonesia, 2015)
ABSTRACT The main problem related to tourism region utilization in the bussiness legal aspects is related to the development and the management of tourism in the region of small islands. Understanding the legal aspects of land will determines the success or failure of the development and management of tourism in the region of small islands. And by understanding the legal principles concerning cooperation, business agreement, tourism area management, specific clauses in the agreement and other things associated with any agreement form, we can say that all of it must be returned on the purpose of article 33 paragraph (3) of the 1945 Constitution to prosperity and justice for the people. Kata Kunci: Pembangunan, Pengelolaan Pariwisata